Φ-Multipliers on Banach Algebras and Topological Modules. (22nd February 2015) - Adib, Marjan
Abstract : We prove some results concerning Arens regularity and amenability of the Banach algebraM φ A of allφ -multipliers on a given Banach algebraA . We also considerφ -multipliers in the general topological module setting and investigate some of their properties. We discuss theφ -strict andφ -uniform topologies onM φ A . A characterization ofφ -multipliers onL 1 G -moduleL p G, whereG is a compact group, is given.